THE RELATIONSHIP BETWEEN FEAR OF FAILURE AND FUTURE CAREER ANXIETY IN FINAL YEAR STUDENTS OF THE FACULTY OF DA'WAH AND COMMUNICATION - Yunisa, Nabila Putri; Noviza, Neni; Fitri, Hartika Utami (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to see the picture of fear of failure, future career anxiety and see the relationship between fear of failure and future career anxiety in final year students of the Faculty of Da'wah and Communication. The research method used is quantitative descriptive with data collection techniques in the form of questionnaires, observation and documentation. The research sample amounted to 79 out of 376 final year students of the Faculty of Da'wah and Communication which were calculated using the slovin formula with an error tolerance of 10%. The results showed that the fear of failure of final year students of the Faculty of Da'wah and Communication 80% were in the moderate category, 9% were in the high category and 11% were in the low category. In future career anxiety 77% were in the moderate category, 10% were in the high category and 13% were in the low category. The results of the relationship between fear of failure and future career anxiety showed an r-count of 0.715, p = 0.000 (p <0.05). The conclusion is that the fear of failure and future career anxiety of final year students of the Faculty of Da'wah and Communication are in the moderate category. Then, between fear of failure and future career anxiety there is a positive relationship and a strong level of closeness.